The Effect of Service and Product Quality on BJB Education Payment Satisfaction - Nita Fitriani; Alis Khofifah (Greenation International Journal of Economics and Accounting, 2024)
Tests conducted on segmental service quality expose that the influence of service quality on customer satisfaction is significant. In different terms, the improved service quality at Bank BJB Unswagati Cash Office Cirebon can increase customer satisfaction. The method of associative quantitative research uses SPSS PC+ for its analysis. Segmental testing of product quality reveals a significant effect of product quality on customer satisfaction. The more Bank BJB Unswagati Cirebon Cash Office provides good product quality, the higher the level of customer satisfaction. Overall, the findings concluded that the simultaneous influence of service and product quality on customer satisfaction positively and significantly impacted Bank BJB Unswagati Cirebon Cash Office. This shows that improvements in both service and product aspects can simultaneously increase the level of satisfaction obtained by customers in the institution.